2018
DOI: 10.1177/1178223418758031
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data on Health-Related Quality of Life Assessment in Patients With Breast Cancer Receiving Subcutaneous Trastuzumab

Abstract: Purpose:Trastuzumab, a humanized anti-human epidermal growth factor receptor 2 (anti-HER2) antibody delivered intravenously, has revolutionized the treatment of patients with breast cancer overexpressing HER2 protein. Recently, a newer subcutaneous formulation was shown to have comparable efficacy to the initial intravenous trastuzumab. In this study, we aimed to evaluate the impact of subcutaneous trastuzumab on the health-related quality of life (HRQoL) of patients diagnosed with early or metastatic HER2-ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…POLARIS is preceded by other breast cancer registries collecting data from real-world settings, including ATHENA [34], RegistHER [35][36][37][38], SystHERS and MedSIR (ClinicalTrials.gov: NCT03819010). Additionally, a standalone study collecting HRQoL data from patients with HER2+ early or metastatic breast cancer treated with trastuzumab or chemotherapy in routine practice has been published recently [39]. These registries and observational studies comport with the current growing interest in and use of real-world data sources in breast cancer research, particularly those linking electronic health records on treatment and outcomes to prospective cancer registries, to address clinically relevant questions that may not be answered in clinical trials [40].…”
mentioning
confidence: 99%
“…POLARIS is preceded by other breast cancer registries collecting data from real-world settings, including ATHENA [34], RegistHER [35][36][37][38], SystHERS and MedSIR (ClinicalTrials.gov: NCT03819010). Additionally, a standalone study collecting HRQoL data from patients with HER2+ early or metastatic breast cancer treated with trastuzumab or chemotherapy in routine practice has been published recently [39]. These registries and observational studies comport with the current growing interest in and use of real-world data sources in breast cancer research, particularly those linking electronic health records on treatment and outcomes to prospective cancer registries, to address clinically relevant questions that may not be answered in clinical trials [40].…”
mentioning
confidence: 99%
“…Nevertheless, these results, taking into account the good functional level of patients at baseline, are consistent with expectation: QoL analyses showed no deterioration of global health status. Recent reports also showed that patients without comorbidity receiving subcutaneous trastuzumab had less treatment side effects, less upset by hair loss, and higher emotional functioning [15].…”
Section: Discussionmentioning
confidence: 98%
“…Those authors used different HRQoL measures (eg, the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire-Core 30) and compared patients receiving subcutaneous trastuzumab with control patients not receiving subcutaneous trastuzumab. 30 The patients' concern over feeling uncomfortable during the trastuzumab administration and focus on trastuzumab injection alone were similar for both the subcutaneous and intravenous forms; this finding is consistent with the systematic review by Dent et al 15 While nurses seemed to have more concerns over reduced interactions with patients due to their painful experiences or administering injections in private body sites in the subcutaneous form, both physicians and pharmacists reported concerns related to their professional tasks while preparing the dosage form (eg, prescribing, dispensing, preparation) in administration processes. From the physicians' perspective, their major concern was the patient preferences, in terms of safety, effectiveness, cost and convenience 15 rather than efficiency, when deciding the dosage form.…”
Section: Discussionmentioning
confidence: 99%